Prevalence of Helicobacter Pylori among Patients undergoing Gastrodudenoscopy in a Hospital in Western Nepal - Shakya, Raju Prasad; Regmi, Sudeep; Adhikari, Suraj (Journal of Lumbini Medical College, 2017)
Introduction: Helicobacter pylori (H. pylori) related chronic gastritis is a major health problem worldwide, specially in the developing countries. The prevalence of H. pylori infection has been reported to vary between and even within countries. There are limited data on this infection in Western Nepal. Our objective was to study the prevalence of H. pylori infection and its association with presenting complains and upper gastrointestinal diseases. Methods: Medical records of patients undergoing gastrodudenoscopy and biopsy for various upper gastrointestinal symptoms from 1st of January 2015 to 30th of June 2017 were reviewed for presence of H. pylori infection, demographics, indications for gastrodudenoscopy, and histopathology findings. T-test, Chi-square test, and Fisher exact test were applied. Results: Two hundred fifty six patients (135 male and 121 female) with a mean age of 47 (SD = 16.5) underwent gastroscopic biopsy and had an overall H. pylori prevalence of 24.6%. H. pylori infection was most commonly noted between 41 to 60 years of age. Gender did not seem to be significantly associated (p = 0.82) but gastrointestinal bleed was significantly associated with H. pylori infection (p = 0.006). The most common histopathological diagnosis was gastritis followed by gastrodudenitis; however, none of the diagnosis were found to be significantly associated with H. pylori infection. Conclusion: The overall prevalence of H. pylori infection was 24.6% and was most common between 40 to 60 years of age. Heart burn was the most common symptom and gastrointestinal bleed was the only significantly associated symptom with H. pyloriinfection.